Splinting with Composite and Wire: Cheap, Flexible Option for Stabilizing Traumatized Teeth - Shah, Harish Kumar; Sharma, Shivalal; Shrestha, Sajeev; Goel, Khushboo; Subba, Nirupa Thamsuhang (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Trauma to teeth is one of the most serious dental injuries, and it requires correct and timely management for the favorable prognosis. Splinting of teeth is considered best practice to maintain the repositioned tooth in the correct position, provide patient comfort and improve function. Amongst several methods, splinting with composite and wire is an economical, maintainable and flexible option for stabilizing traumatized mobile teeth. This case report shows splinting of teeth with composite and wire of traumatized teeth in a 24-year-old-male with two years follow up.